PENGENDALIAN KUALITAS BIDANG PENDIDIKAN DAN PELATIHAN - Renny Sukmono (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
The sertification of ISO 9001;2008 is a of quality assurance that intended to certify the providers of goods and services. This sertification demand the providers to obtain not only changes in quality to be better but also the improvements. In evaluation phase of a program, control chart is a method that can be used to identificate the achiement in quality and what do to make it even better. This control chart is widely used in industrial sector. But now day the other field also using this method, like in public service or education system. The avarage control chart and standard deviation control chart will be used to review the training program entitled as training of planning and budgeting, to make sure that the program was under control or not. It is already known that the implementation of the training program was well controlled in average but it wasn;t good enough in standard deviation valuation. This coclusion indicating there are several things that should be improved by the education and training center of budgeting and treasury as the executor of this training program. Thought the research and analysis, the program was out of control because the lack of stakeholder’s commitment in sending the training participants. This training program is slated for the head of public subsection around ministry of finance , but the stakeholder sent not only the public subsection head, but also the common employees and even the office’s prime leader. In order to prevent the same mistakes in the next program, the education and training center of budgeting and treasury should strengten the commitment with its stakeholder and properly constructed the similiar training program that specially intended for order job class, like common employees and the office’s prime leader. The unmanageable process in standard deviation is pointing out a significant number of diversity in participants’ average grades of pretest and posttest. The pretest mark has an important role because it will show the participant’s early knowledge about the training lesson. After the detailed examination in this research , it is stated that particpant’s origin institute had quite a lot influence in their pretest grade. The participants from treasury departement had higher marks than order departements. Actually this is a proper case because the works in treasury departement are closely realted to planning and budgeting, which is the program’s main lesson. Tocope with this metter, the education an training center of budgeting and treasury have to grouping the participants in two large clusters : treasury departement’s employees and non-treasury departement’s emloyees.